Barriers to Smoking Cessation Among Drug-Resistant Tuberculosis Patients in South Africa - Zifikile Phindile Shangase; Joyce Mahlako Tsoka-Gwegweni; Catherine O. Egbe (Ubiquity Press, 2017)
Background: Drug-resistant tuberculosis (DR-TB) remains a significant cause of morbidity and mortality. The long-term health effects of smoking and the risk of adverse TB outcomes, including increased periods of infectiousness, have been reported among DR-TB patients in South Africa. Objectives: This study aimed to identify the barriers to smoking cessation among DR-TB inpatients at a hospital in Durban, South Africa. Methods: A qualitative design using in-depth interviews with a purposive sample of 20 DR-TB inpatients was employed. The sample included 15 men and 5 women aged 18-70 years who self-identified as smokers. Open-ended questions were used to explore barriers militating against smoking cessation among this sample. Data were analyzed with the aid of the software QSR NVivo10. Findings: Personal and structural-level barriers (factors) to smoking cessation were identified. Personal factors included addiction and non-addiction-related barriers. Addiction-related barriers included smoking history, cravings for a cigarette, smoking as part of a daily routine, and failed quit attempts. Non-addiction-related barriers included lack of knowledge about quit strategies, psychosocial stress, lack of the willpower to quit smoking, and the influence of peers. Structural barriers included ineffective health education programs, lack of extramural activities when on admission in hospital leading to a lot of spare time, lack of smoking cessation interventions, and access to cigarettes within and around the hospital environment. Patients expressed interest in smoking cessation and conveyed their frustration at the lack of appropriate support to do so. Conclusions The findings reiterate the need for smoking cessation intervention to be incorporated as an integral component of DR-TB management in South Africa. Many patients expressed an interest in pharmacological aids and psychological support to help them to quit smoking. Additionally, offering extramural activities and enforcing smoke-free policies in hospital facilities will help to reduce patients' access to cigarettes while at the hospital.